2016
DOI: 10.1210/jc.2015-3295
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Valvular Surgery in Carcinoid Heart Disease: An Observational Cohort Study

Abstract: Valve surgery improved functional class and resulted in RV reverse remodelling with improved survival rates at 2 y compared with those not proceeding to operation. These data highlight the importance of close collaboration between NET clinicians, cardiology, and cardiothoracic surgery teams. Early referral can improve functional capacity but more research is needed to define the selection of appropriate candidates and randomized data are needed to define the effect of surgery on prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…Post-operative mortality is mainly due to the carcinoid disease itself. 15,16 conclusIon Our case represents an unusual and early presentation of carcinoid syndrome in a 27-year-old woman who had severe pulmonary and tricuspid disease with right atrial enlargement at the time of diagnosis. She underwent successful valvular replacement.…”
Section: Discussionmentioning
confidence: 83%
“…Post-operative mortality is mainly due to the carcinoid disease itself. 15,16 conclusIon Our case represents an unusual and early presentation of carcinoid syndrome in a 27-year-old woman who had severe pulmonary and tricuspid disease with right atrial enlargement at the time of diagnosis. She underwent successful valvular replacement.…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, anasarca edema and the need for intravenous diuretics prior to cardiac surgery independently predicted perioperative mortality. The lack of prognostic significance in the time from diagnosis to surgery has been reported elsewhere [33]. A possible explanation for this phenomenon is that it may reflect the progression of the underlying malignancy, which affects survival to a greater extent than the progression of RHF.…”
Section: Current Trends and Unresolved Issuesmentioning
confidence: 87%
“…In another recently published study, Edwards et al [33] reported the outcomes of patients who underwent cardiac surgery for CHD at a single center between 2005 and 2015. Patients with CHD were referred for surgery if they had 1 of the following indications: (a) a stable carcinoid tumor load, (b) severe valvular dysfunction, or (c) exercise-limiting symptoms.…”
Section: Chd Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In CaHD, the right-sided heart valves are primarily affected because of their direct exposure to circulating blood serotonin, leading to right heart failure. Once patients with CaHD develop heart failure symptoms, the only effective treatment option is valve surgery, which has shown to decrease mortality and improve functional symptoms [3][4][5][6][7][8]. Majority of those patients required both tricuspid valve (TV) and pulmonary valve (PV) surgeries, preferably replacement [7,9].…”
Section: Introductionmentioning
confidence: 99%